Historical, Legal And Social Analysis Of Mandatory Class Attendance At The Bolivian Public University - Richard, Enrique; Maillard Bauer, Pedro (Ius Humani. Jornal do direito, 2024)
Compulsory attendance at theoretical classes (AOCT) was abolished in most of the public universities in Latin America as a result of the University Reform of 1918. The idea was that good teachers had full classrooms and mediocre teachers the same, evidencing their condition. In recent decades, Bolivia gradually implemented the AOCT again. Here the degree of legitimacy and legality of the AOCT in the public universities of Bolivia is analyzed. The historical background of the issue, national legislation and human right were studied. Surveys were conducted with university teachers. We conclude that the AOCT has questionable overtones of legality and shades of coercion, extortion and intimidation. The instituted norms of AOCT are contrary to laws of a higher order and to the reformist principles themselves. They lack legitimacy since they violate the epistemological principles of the 1918 Reform. The AOCT violates the principles of democracy, equity, inclusion, right to work and quality of teaching, among others.